The Effect of Combined and Core Stability Training Program with Protective Measures on Selected Variables of Physical Fitness of Junior and Young Volleyball Players during the Coronavirus Pandemic - Ali Fatahi; Razieh Yousefian Molla; Mitra Ameli; Davood Khezri (Biyumikānīk-i varzishī)
Objective: The aim of this study was to investigate the effect of a combined and core stability training program with protective measures on selected variables of physical fitness of junior and young volleyball players during the coronavirus pandemic. Methods: 15 male volleyball players [18±1.06 yrs.] after the end of the first quarantine period and then after a 12 weeks period of combined and core stability training program emphasizing on physical fitness exercises in compliance with all health protocols, as pre-test and post-test of selected key factors, performed physical fitness including lower limb strength, upper limb and abdomen endurance, as well as flexibility tests. Descriptive statistics, Shapirovik test and paired t-test were used for statistical analysis (p≤ 0.05). Results: The results of the present study showed that there was a statistically significant difference in the variables of upper limb and trunk muscle endurance as well as muscle flexibility, but in the lower limb strength variable, this difference was not observed in both pre-test and post-test levels. Conclusion: Volleyball coaches and players can benefit from combination and core stability training with health protocols to maintain and improve fitness during the coronavirus epidemic.